An ethnographic study of participant roles in school bullying. Issue 3 (22nd January 2014) - Gumpel, Thomas P.; Zioni‐Koren, Vered; Bekerman, Zvi
<x xml:space="preserve">Abstract</x> An ethnographic study in a 10th grade remedial class was undertaken in order to discern patterns of school bullying. Twenty 10th graders were observed over the course of one academic year as they interacted with their peers and teachers. The observations helped us identify dispositional and situational factors which influenced participant roles. In‐depth interviews of students involved in school bullying showed how participants interpreted and explained their classroom behaviors. The analysis of the data gathered allowed the identification of four main actor roles recognized in the existing literature on bullying—the pure victim, the pure bully, the provocative‐victim, and the bystander—as well as the differentiation between aggressive bullies and the bully managers. Most roles fluctuated according to specific circumstances and often appeared to be moderated by the teacher's management style and contextual variables. Some pupils assumed different roles in different contexts, sometimes changing roles within or between episodes. Teacher personality and style also had an impact on the frequencies and types of aggression and victimization. The use of an ethnographic research paradigm is discussed as an important supplement to positivistic studies of school bullying. Aggr. Behav. 40:214–228, 2014. © 2014 Wiley Periodicals, Inc.